Konsep Diri Pada Waria Dalam Perspektif Humanistik (Studi Analisa Kasus Klien “M”) di Desa Pajar Bulan Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Anggi Suryaningsi; Komaruddin Komaruddin; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This study entitled Self-concept of transgender women from a humanistic perspective (a case analysis study of "M" clients) in Pajar Bulan Village, Kec. Tanjung Batu Regency. Ogan Ilir. Waria have been known since ancient times. The Qur'an mentions sexual deviations committed by his people, the Prophet Lut. Deviant sexual behavior that has started to harm is homosexual. The phenomenon of waria is a real explanation that cannot be denied its existence in society. However, not many people know the real life background of transgender people. This research is a qualitative research with a case study type. Qualitative research method is a descriptive research and tends to use analysis. When analyzing self-concept in transgender women, the researcher uses a humanistic perspective to see how a client's self-concept and reasons for turning into a waria are based on the results of interviews conducted by researchers. waria. The self-concept of waria can be analyzed through a humanistic perspective. Where this humanistic perspective is able to see human life as humans themselves see their lives. The condition of client "M" began when he was a teenager aged 15 years because of his behavior and environmental factors. cellphone but the family does not respond to his wishes. This is a hard trigger for client "M" to change himself as a waria and plus he has no job so that family factors as well as finances are the reason he becomes a waria.